Effects of marine protected areas on fisheries: the case of Sao Paulo State, Brazil - Rolim, Fernanda A. [UNESP]; Avila-da-Silva, Antonio O. (Univ Catolica De Valparaiso, 2016)
In 2008, the government of the Sao Paulo State, Brazil, established marine protected areas (MPAs) along its entire coast. Pair trawling was banned from most of these areas ever since. This study investigated how these MPAs influenced on pair trawling fleet's operational patterns and landings from 2005 to 2012 as well as on the other fleets dynamics. Landings of pair trawlers per unit effort remained stable, however, they had to look for farther fishing grounds and capture deeper and less profitable species, changing their landing composition and reducing income. Gillnet fleet, particularly, has intensified fishing in MPAs and showed an increase in catches of some species that was once targeted by pair trawlers. In this case, MPAs management acted more towards a territorial management, protecting artisanal fisheries, than in the protection of fisheries resources.
Keywords: industrial fisheries; marine spatial planning; ecosystem approach to fisheries management; fishery; socio-economics; southwest Atlantic Ocean